Transatlantic regulatory cooperation: the shifting roles of the EU, the US and California (Cheltenham, 2011)
"This well-documented book analyzes the possibilities and constraints of regulatory cooperation between the EU and the US (particularly California) with a specific focus on environmental protection, food safety and agriculture, biosafety and biodiversity. Transatlantic Regulatory Cooperation features eleven original essays by leading academics of regulation on both sides of the Atlantic. They explore topics such as the impact of federalism on regulatory policies both within the US and Europe, the transatlantic dynamics of water policy, climate change, pesticide and chemical regulation, and biotechnology. A primary focus of this timely study is on the shifting roles of California and the EU as regulatory leaders and ITS impact on future regulatory cooperation across the Atlantic. This informative book will appeal to graduate and postgraduate students, as well as academics and researchers in international relations, business, law and economics who are working on regulatory issues. The policy community which focuses on regulation and transatlantic regulatory relations will also find it an important resource."